Survey: awareness level among paddy farmers toward health risk on pesticides application at Kampung Dulang Kechil, Yan, Kedah / Mohammad Azwan Fahmie Zulkurnain - Zulkurnain, Mohammad Azwan Fahmie (Faculty of Plantation and Agrotechnology, 2018)
Paddy or its scientific name is Oryza sativa L. is the important crop that human consumes in the term of rice when it done processed modernly or traditionally. Over the next fifty years, the world population is predicted to grow fifty percent to nine billion people by 2050, the world food demand such as paddy will be double for the population (Kumari & Reddy, 2013). According to Kumari & Reddy (2013), To get the good and high yield, the farmer start to use the chemical pesticides to their crop but at the same time they forgot to think about their health risk on the pesticides used. In order to achieve sufficient supply of paddy production, the farmers just apply the pesticides without aware the health risk that they can get from their action. Awareness is important factor to evaluate the farmers to know about their knowledge toward pesticide application on paddy field. The aims of this study are to identify the awareness level of farmers toward health risk on the pesticides application in paddy farming, to determine the rate of accident among the farmers and to identify the relationship between awareness level and rate of accidents toward health risk on pesticides used. The research was conducted to paddy farmers at Kg. Dulang Kechil, Yan Kedah with the total respondent 80 individual out of 100 in a population. The data have been collected through distributed questionnaire and face to face interview. SPSS have been used to analyze the data through descriptive and correlation analysis. The result was found that the awareness level among the paddy farmers is high and rate of accident along using the pesticides at medium level. In addition, this study also shows that there are a relationship between awareness factor and rate of accident toward health risk on pesticides usage. As a conclusion, the awareness about health risk on pesticides application can help farmers to reduce the rate of accident and improve the paddy farmers’ health condition.